Study of choroidal thickness variations after ingestion of a taurine and caffeine-containing energy drink. (June 2021) - Arej, Nicolas; Azar, Georges; Salviat, Flore; Alonso, Anne-Sophie; Zuber, Kevin; Metten, Marie-Astrid; Salomon, Laurence; Vasseur, Vivien; Mauget-Faÿsse, Martine
Summary: Background & aims: Choroidal thickness can undergo considerable variations in response to different substances. The aim of this study was to assess the change in choroidal thickness after the ingestion of taurine and caffeine contained in the Red Bull energy drink. Methods: Enhanced Depth Imaging - Spectral Domain Optical Coherence Tomography was used to measure subfoveal choroidal thickness (SFCT) variations in healthy volunteers at several time points after drinking a Red Bull can (25 cl). Results: Forty eyes of 20 volunteers were enrolled. A significant reduction in SFCT (−14 μm, p < 0.0001) occurred at 1 h after the Red Bull intake, and was even more important (−20.14 μm, p < 0.0001) in eyes with particularly thick choroids (≥ 395 μm). SFCT measurements at 4 h were comparable to baseline. Conclusions: A concomitant ingestion of caffeine and taurine can induce a transient choroidal thinning that is more marked in eyes with thick choroids. Registration number of clinical trial: NCT02856256.